Assessing Management Supports to the Internal Audit System in Bo District Council, Sierra Leone - Sheriff, Sualiho (New Innovations in Economics, Business and Management Vol. 9, 2022)
The study intended to assess one of the daunting challenges facing the effective operations of Local Councils in Sierra Leone particularly the Bo District Council is the quality of support services that drive accountability in the use of scarce financial resources. The research was carried out in the Bo District Council in Sierra Leone's Southern Region. Bo District Council consists of 16 Chiefdoms, 25 Councilors, 3 Paramount Chiefs, 25 Wards, 16 Committees, 11 Constituencies, and 13 Core Staff Members. The study objectives were; i) to assess the level of respondents' perceptions of management support to the internal audit system; ii) to identify the scale of management support to the internal audit effectiveness, and iii) to establish the relationship between management support and internal audit effectiveness. The 13 core staff members were chosen using a stratified sampling process. The study used a descriptive design, with qualitative and quantitative approaches used to discuss the findings. The Crumb Alpha Test was used to conduct the reliability test, which was found to be valid at 0.765. The study's primary findings include: lack of complete support for the audit committee, lack of independence of internal audit system and insufficient budget allocation.